Big Data Analytics for Optimizing Multimodal Supply Chains in the Maritime Industry - Chanra Purnama; Marudut Bernadtua Simanjuntak; Malau, April Gunawan (TEMATIK, 2024)
This research investigates the integration of big data analytics in optimizing multimodal supply chains within the maritime industry. Focusing on efficiency, flexibility, reliability, and visibility, the study examines 100 cadets at a maritime institute, using qualitative research methods and descriptive analysis. Findings reveal a critical need for knowledge and skills, infrastructure and resources, organizational culture and support, and regulatory compliance. The research underscores the importance of investing in training and development, infrastructure, and fostering a culture that values innovation and data-driven decision-making. By addressing these needs, organizations can enhance their readiness to adopt and implement big data analytics, improving the efficiency and sustainability of their supply chains. The study contributes to the understanding of how big data analytics can be leveraged to enhance supply chain performance in the maritime industry.